2013
DOI: 10.1097/mca.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy of monocytes attenuates the vulnerability of coronary atherosclerotic plaques

Abstract: Autophagy of PBMs is involved in the pathogenesis of plaque vulnerability and subsequent plaque rupture. Enhancing the autophagy of PBMs may be a new therapeutic target for stabilizing atherosclerotic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…17 Recently, multiple lines of evidence have revealed that both ER stress and autophagy are implicated in the pathogenesis of atherosclerotic plaque vulnerability and subsequent plaque rupture. 12,18,19 However, the interaction of ER stress and autophagy in the progression of atherosclerosis induced by hyperglycaemia is currently unknown. In the present study, we investigated the roles of ER stress and autophagy in gly-HDL-induced macrophage apoptosis and the crosstalk between them in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, multiple lines of evidence have revealed that both ER stress and autophagy are implicated in the pathogenesis of atherosclerotic plaque vulnerability and subsequent plaque rupture. 12,18,19 However, the interaction of ER stress and autophagy in the progression of atherosclerosis induced by hyperglycaemia is currently unknown. In the present study, we investigated the roles of ER stress and autophagy in gly-HDL-induced macrophage apoptosis and the crosstalk between them in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…With high anesthetic efficacy, inhalation anesthetics, which allow for easy control of the depth of anesthesia, have been widely applied in a clinical setting for >170 years (1,2). In the USA, the number of individuals receiving general anesthesia reaches 40 million each year.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that AMPK activity and autophagy of monocytes were significantly decreased in ACS patients compared with those in the SAP and control groups. As described in our previous study, autophagy of PBMs in patients with coronary heart disease increases the vulnerability of atherosclerotic plaques [5]. AMPK can regulate autophagy by activating autophagic regulatory protein in the initial step of autophagy-mediated degradation [10].…”
Section: Discussionmentioning
confidence: 98%
“…Our data showed that the expression levels of beclin-1 and ATG7 were low in circulating monocytes. Autophagy may be more likely to contribute toward attenuating the vulnerability of atherosclerotic plaques [5]. Monocytes are the key immune cells that play a significant role in atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation